Mechanical testing of cephalomedullary nail lag screws after the addition of hydroxyapatite substitutes. Issue 4 (3rd December 2021) - Nakajima, Takayuki; Aoki, Yasuchika; Watanabe, Atsuya; Inoue, Masahiro; Yamaguchi, Satoshi; Nakamura, Junichi; Matsuura, Yusuke; Hagiwara, Shigeo; Himeno, Daisuke; Ohtori, Seiji
Abstract: Objective: To compare the effects of 3 implant designs, with and without hydroxyapatite reinforcement, on push/pull-out strength and rotational torque. Methods: Three implant designs (Gamma 3, INTERTAN, and PFNA-II) were selected for comparison. A hydroxyapatite cylinder (NEOBRACE) was used to reinforce the interface between the femoral head and the lag screw. Maximum push-out strength, maximum pull-out strength, and peak rotational torque were measured in cellular blocks mimicking osteoporotic cancellous bone, with and without NEOBRACE. Results: In the push-out test, INTERTAN produced a significantly higher push-out strength in osteoporotic bone density cellular blocks than the other lag screws and blades ( P  < .05). With the addition of NEOBRACE, push-out strength was significantly higher for INTERTAN and PFNA-II ( P  < .05) than for the non-NEOBRACE group. In the pull-out test, INTERTAN produced a significantly higher pull-out strength in the osteoporotic bone density cellular blocks than did the other lag screws and blades ( P  < .05). With the addition of NEOBRACE, the pull-out strengths of INTERTAN and Gamma 3 versus those of the non-NEOBRACE group significantly increased ( P  < .05). In the rotational torque test, INTERTAN produced significantly greater rotational torque in the osteoporotic cellular blocks than the other lag screws and blades ( P  < .05). The addition of NEOBRACE resulted in a significant increase in rotational torque only for INTERTAN ( P  < .05). Conclusion: The use of NEOBRACE supported an increase in push/pull-out strength and rotational torque, especially in systems with a relatively increased bone or implant interface area. Level of Evidence: Level V